Peer effect sobre o desempenho escolar: um estudo de caso na escola de educação profissional Adriano Nobre no Ceará - Cruz, Francisco Evangelista Maia (2022)
This work aims to verify the effect that the presence and performance of students from private schools have on the academic performance of other students in high school, both belonging to the same class. With this, we seek to contribute to the education literature by finding the peer effect of these students on school performance, measured by proficiency in Portuguese and Mathematics tests, hitherto not addressed in other studies. In addition, it was decided to carry out an analysis of heterogeneous effects in order to identify whether the effect differs between boys and girls. Ordinance 105/2009 issued by the Ceará State Department of Education authorizes the enrollment of twenty percent of students from the ninth grades of the private network in state vocational education schools. Through the academic SIGE, it was possible to obtain administrative data regarding the enrollment of students, allowing the identification of those who came from private schools present in each class for the period from 2009 to 2019. From this information, a cross-reference was made with the database of the SPAECE to obtain the socioeconomic and educational characteristics of these students. From the results, it was possible to observe a positive peer effect, measured by the average of the proficiencies of students from private schools, on the students' proficiency in mathematics. In addition, it was found that only the effect of peers in the group of students from public schools is significant for girls.